2014
DOI: 10.1016/j.jss.2014.05.052
|View full text |Cite
|
Sign up to set email alerts
|

Relative value units poorly correlate with measures of surgical effort and complexity

Abstract: Background The relationship between procedural relative value units (RVUs) for surgical procedures and other measures of surgeon effort are poorly characterized. We hypothesized that RVUs would poorly correlate with quantifiable metrics of surgeon effort. Methods Using the 2010 ACS-NSQIP database, we selected 11 primary CPT codes associated with high volume surgical procedures. We then identified all patients with a single reported procedural RVU who underwent non-emergent, inpatient general surgical operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 14 publications
(13 reference statements)
2
59
0
Order By: Relevance
“…9 Shah et al analyzed 11 different high-volume elective general surgical procedures and found that the current RVU system poorly co-related with individual operative times and morbidity of procedures, and thus are a poor index reflective of surgeon's work and effort. 10 Our study has several limitations. It is important to note that the current analysis is aimed at understanding the financial constraints of the current RVU system for singlecomponent and double-component revision TKAs.…”
Section: Discussionmentioning
confidence: 91%
“…9 Shah et al analyzed 11 different high-volume elective general surgical procedures and found that the current RVU system poorly co-related with individual operative times and morbidity of procedures, and thus are a poor index reflective of surgeon's work and effort. 10 Our study has several limitations. It is important to note that the current analysis is aimed at understanding the financial constraints of the current RVU system for singlecomponent and double-component revision TKAs.…”
Section: Discussionmentioning
confidence: 91%
“…Compared with that of United States’ RBRVS, the underestimation of a spinal physician’s labor was even more significant. Concerns that the RVs under RBRVS may not accurately reflect a surgeon’s work, productivity or value is not surprising, and has already been an issue also in other surgical specialty societies8). The problem is, that not much attention has been paid for this problem for a long period of time in our surgical society and maybe this lack of interest for proper reimbursement might have led to this discrimination of RVs.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate physicians' output, hospitals must measure surgical costs and values. These values by necessity reduce a multitude of nominal, ordinal, and numeric values to something that can be measured with an interval scale; they are subjectively determined and fail to represent physicians' work comprehensively . Any performance‐based payment system lets each surgical case generate a certain number of relative value units per unit time, depending on the evaluation of case complexity, which is subjectively determined or, rather, chosen .…”
Section: Educational Concerns Generated By Applying Npm To Health Carementioning
confidence: 99%